1996
DOI: 10.3758/bf03213094
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of visual attention: Perceptual sensitivity and response latency

Abstract: Studies of the spatial distribution of visual attention have shown that attentional facilitation monotonically decreases in a graded fashion with increasing distance from an attended location. However, reaction time (RT) measures have typically shown broader gradients than have signal detection (SD) measures of perceptual sensitivity. It is not clear whether these differences have arisen because the stages of information processing indexed by RT measures are different from those indexed by SD measures, or whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
77
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 63 publications
12
77
0
Order By: Relevance
“…For example, both Depth Perception disparity thresholds and response times were correlated across the three viewing conditions; however, thresholds and response times did not cross-correlate with each other. This observation supports the notion that response speed and perceptual sensitivity are separable facets of performance (Handy, Kingstone, & Mangun, 1996;O'Connor & Burns, 2003), even when measured within the same task. In addition, the score of Near-Far Quickness correlated with the Depth Perception Reaction Times, but not the Depth Perception thresholds.…”
Section: Perceptual and Visual-motor Abilities As Measured By The Sensupporting
confidence: 77%
“…For example, both Depth Perception disparity thresholds and response times were correlated across the three viewing conditions; however, thresholds and response times did not cross-correlate with each other. This observation supports the notion that response speed and perceptual sensitivity are separable facets of performance (Handy, Kingstone, & Mangun, 1996;O'Connor & Burns, 2003), even when measured within the same task. In addition, the score of Near-Far Quickness correlated with the Depth Perception Reaction Times, but not the Depth Perception thresholds.…”
Section: Perceptual and Visual-motor Abilities As Measured By The Sensupporting
confidence: 77%
“…In addition, shape matching between a cued and an uncued color singleton becomes degraded when the distance between them is reduced (28). Furthermore, single-cell recordings in monkeys (8,10,29) and event-related potential and functional MRI studies in humans (14,30,31) hint at the possibility that neural enhancement in the focus of attention may be accompanied by neural suppression of the immediate surround.In contrast, other behavioral and electrophysiological studies have found simple monotonic gradients of attention (18)(19)(20)(21)(22). However, these monotonic gradients may reflect an insufficiently dense sampling of the attentional gradient or the use of measures that conflate perceptual and postperceptual mechanisms of attention.…”
mentioning
confidence: 73%
“…In contrast, other behavioral and electrophysiological studies have found simple monotonic gradients of attention (18)(19)(20)(21)(22). However, these monotonic gradients may reflect an insufficiently dense sampling of the attentional gradient or the use of measures that conflate perceptual and postperceptual mechanisms of attention.…”
mentioning
confidence: 73%
See 2 more Smart Citations